Temporal trend and characteristics of notifications of self-inflicted and interpersonal violence in the transgender population in Brazilian municipalities, 2015-2022 - Kelly Roberta Estrela Marinho Neto; Jeane Tomazelli; Vania Reis Girianelli (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To analyze the temporal trend and characteristics of notifications of violence among the transgender population from 2015 to 2022 in Brazilian municipalities. Methods This was a repeated panel epidemiological study, based on violence incidents reported among the transgender population aged 20 to 59 years, available in the Notifiable Health Conditions Information System. An annual temporal trend analysis was performed by means of generalized linear regression, using the Prais-Winsten method and spatial distribution of notifying municipalities in Brazil. Results Notifications of violence in the transgender population decreased during the period (1.7%; β = -0.07; p = 0.010), but there was an increase in the number of notifying municipalities (45.8%), self-inflicted violence (28.9%; β = 2.21; p < 0.001) and sexual violence (β = 0.79; p < 0.001). The majority of perpetrators were male and in an affective relationship, especially with transgender women (43.4%; p < 0.001). Conclusion Notification of violence does not yet fully reflect the reality of this population, but it represents the first step towards visibility and addressing the issue.